Plateau lavas and diabase dikes of northwestern Newfoundland - Strong, D. F. (Geological Magazine, 1974)
Summary Thin undeformed tholeiitic plateau lavas and associated diabase dikes occur intermittently along the western margin of the Appalachian mountain system, and are clearly exposed at its northern extremity in northwestern Newfoundland. In Newfoundland there are consistent chemical differences between the diabase dikes and the plateau lavas which indicate that they were derived from different primary magmas. These differences, along with apparent age discrepancies, could be taken as supporting suggestions of several periods of continental rifting, but such an interpretation is not favoured by the present author.